2005
DOI: 10.1002/jor.20020
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed ultrasound treatment accelerates the repair of Achilles tendon rupture in rats

Abstract: A rat tenotomy model was used to investigate the effect of combined conservative management and pulsed ultrasound (PUS) on the repair of tenotomized Achilles tendon. Hemitenotomy of right medial Achilles tendon was performed in 48 rats without suture, and patella tenotomy was performed to mimic immobilization and limb disuse of an injured limb. PUS and sham PUS were applied to the healing wound for the treatment group and control group for 5 min, 3 times per week for 2 or 4 weeks, respectively. Tensile tests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
21
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 44 publications
6
21
0
8
Order By: Relevance
“…The ability of the tissue to withstand high stress levels is related to the percentage of collagen matrix in the tissue and collagen matrix maturity. 20 Our results are in agreement with those of Yeung and colleagues, 35 who found a more mature scar tissue with a more parallel arrangement of collagen fiber bundles in the tendon that had undergone ultrasound treatment, especially after 4 weeks. These authors 35 also reported improved biomechanical properties, with significantly higher ultimate tensile strength and stiffness in the ultrasound treatment group after 2 and 4 weeks of LIPUS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ability of the tissue to withstand high stress levels is related to the percentage of collagen matrix in the tissue and collagen matrix maturity. 20 Our results are in agreement with those of Yeung and colleagues, 35 who found a more mature scar tissue with a more parallel arrangement of collagen fiber bundles in the tendon that had undergone ultrasound treatment, especially after 4 weeks. These authors 35 also reported improved biomechanical properties, with significantly higher ultimate tensile strength and stiffness in the ultrasound treatment group after 2 and 4 weeks of LIPUS.…”
Section: Discussionsupporting
confidence: 91%
“…20 Our results are in agreement with those of Yeung and colleagues, 35 who found a more mature scar tissue with a more parallel arrangement of collagen fiber bundles in the tendon that had undergone ultrasound treatment, especially after 4 weeks. These authors 35 also reported improved biomechanical properties, with significantly higher ultimate tensile strength and stiffness in the ultrasound treatment group after 2 and 4 weeks of LIPUS. Cunha et al 3 reported similar results and showed that pulsed ultrasound had a stimulatory effect on the rate of tissue regeneration in a ruptured calcaneus tendon, with improved collagen synthesis and better alignment and aggregation of the collagen fibers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there is no promising animal or clinical evidence that US can help repair muscle injuries [20][21][22][23] , there is plenty of evidence showing the effects of US in collagen repair and re-synthesis 25,[33][34][35][36][37][38][39][40][41] . The use of US in the present clinical case was oriented at improving muscle collagen extracellular matrix (CEM) repair, based upon US effects on fibroblast proliferation and collagen synthesis 25,39) .…”
Section: Discussionmentioning
confidence: 99%
“…Este estudio confirma trabajos previos que describen una aceleración de la regeneración tendinosa gracias al uso de ultrasonido (Grass et al;Bassoli;da Cunha et al, 2001;Berná-Serna et al, 2005;Yeung et al, 2006). Por otro lado, se demuestra la presencia de fibroblastos activos en la secreción de matriz extracelular con una rá-pida proliferación celular, lo que lleva, finalmente, a una aceleración de la regeneración tendinosa, posterior a una lesión.…”
Section: Discussionunclassified